Papel da vitamina D3 em doenças neurológicas e avaliação pré-clinica na demência esporádica do tipo Alzheimer - Rodrigues, Marília Valvassori (2019)
Dementia is a brain disorder characterized by decline of some function, resulting in deficits in memory functioning and in dialy cognitive tasks. Evidence has emerged that Vitamin D3 (VD3) has innumerable functions in the Central Nervous System (CNS) such as: neuroprotection and neuroimmunomodulation, besides having antioxidante function. Thus, the objective of our study was to investigate the role of VD3 on memory and oxidative stress in a model of sporadic dementia of Azlheimer’s type (SDAT), induced by intracerebroventricular administration of Streptozotocin (ICV-STZ). In addition, a literature review was also performed on the assossiation of VD3 in some neurogocnitive disorders such as: Alzheimer’s Disease (AD), Parkinson’s Disease (PD), Multiple Sclerosis (MS) and Schizophrenia (SZ). The analyzes where performed in through two experiments. In the first experimental research, 56 adults male Wistar rats were used, and in the second experimental research, 40 adults male Wistar rats were used. Both animals were submitted to a cirurgical procedure for the administratios of ICV-STZ (3 mg/ kg), to in a order to induce demetia in these animals, and after birding for a recovery of 3 days and after oral doses of VD3 for 21 days. In the forst experiment the animals were divided into 8 groups: CTL (control), CTL + 12,5 µg/kg, CTL + 42 µg/kg, CTL + 125 µg/kg, STZ (streptozotocin); STZ + 12,5 µg/kg, STZ + 42 µg/kg, STZ + 125 µg/kg. In the second experiment, animals were divided into 4 groups: CTL, CTL + 125 µg/kg, STZ, STZ + 125 µg/kg. The results obtained in theses experiments demonstrated in relation to the activity of the enzyme acetylcholinesterase (AChE) in cerebral cortex supernatant a significant increase in the groups if aniumals that receiving ICV-STZ, with the doses of 42 µg/kg e 125 µg/kg of VD3 were able to prevent this increase, whereas with regard to AChE activity in cerebral cortex of synaptossomes, a significant increase was alsoobserved in animals receiving ICV-STZ, with a dose of 125 µg/kg of VD3 capable of of preventing this increase. Moreover, in theses same animals an increase in thiobarbituric acid levels (TBARS) was found, and the dose of 125 µg/kg able to prevent, similarly with regard to carbonil protein levels in the animals with ICV-STZ a significant increase, with doses 12,5 µg/kg, 42 µg/kg e 125 µg/kg of VD3 being able to prevent. Regarding the levels of reative species of oxigen (ROS, we did not observed significant difference in the animals that dementia. In congtrast, we observed a reduction in Vitamin C levels, however VD3 was not able to predict this result. Regarding reduced Gluathione (GSH), a significant reduction was observed in animals receiving ICV-STZ, with a dose of 125 µg/kg of VD3 capable of preventing in contrast, an ncrease an oxided Gluthatione (GSSG) levels was found. The doses of 12,5 µg/kg, 42 µg/kg e 125 µg/kg of VD3 were able to prevent this increase. Likewise, a significant increase was observed in relation to the thiol groups in the animals receiving ICV-STZ doses of 42 µg/kg e 125 µg/kg of VD3 capable of prevention. Finally, regarding behavioral test results, treatment with VD3 reversed animal damage caused by ICV-STZ in the Morris Water Mazze (MWM) test, in both time spent in the quadrant target, a significant increase was observed in animals receiving ICV-STZ, with a dose of 125 µg/kg of VD3 being alble to prevent. Regarding the number of intersections in the target quadrant, no significant difference was observed in between the groups. In the time spent in the quadrant something during the test day a significant reduction was observed in the animals received ICV-STZ, with the 125 iµg/kg of VD3 being albe to prevent this reduction and finally, regarding the number of crossings in the target quadrant in test day no difference was observed between the groups. These results demonstrat e the high levels of oxidative stress, in adittion to behavioral decline presented by animals with dementia, and the treatmente of VD3 can prevent this decline. Regarding to literature review on neurocognitive diseases (AD, PD, MS and SZ), it is believe that decrease levels of VD3 may be related to the onset of theses diseases. In contrast, the supplementation wich this Vitamin can have beneficial effects by the preventing the damage caused by these diseases. Thus, we can suggest that this compund can be used as a new suppoting strategy to control and prevent conginitive dysfunctions associasted with neurodegenerative and neurocognitive disorders.